Race, ethnicity, and the use of regional anesthesia in cancer patients undergoing open abdominal surgery: A single-center retrospective cohort study - Owusu-Agyemang, Pascal; Feng, Lei; Porche, Vivian H.; Williams, Uduak U.; Cata, Juan P. (Frontiers in Medicine, 2022)
Background Where applicable, regional anesthesia has been shown to be superior to opioid or non-opioid analgesic modalities alone. However, some studies have shown ethnic-based disparities in the use of regional anesthesia in patients undergoing surgical procedures. In this study of patients who had undergone major oncologic surgery, our main objective was to compare the use of regional anesthesia between patients of different ethnicities. Methods A retrospective review of adults who had undergone major open abdominal surgical procedures between 2016 and 2021 was performed. Logistic regression models were used to assess the association between baseline patient characteristics and the use of regional anesthesia. Results A total of 4,791 patients were included in the analysis. The median age was 60.5 years [interquartile range, 49, 69], the majority were female (65%), and of American Society of Anesthesiologists Physical Status Class (ASA) 3 (94.7%). Regional anesthesia was used in 2,652 patients (55.4%) and was not associated with race or ethnicity (p = 0.287). Compared to White patients, the odds of regional anesthesia use in other racial/ethnic groups were: Asian {odds ratio (OR) 0.851 [95% confidence interval (CI), 0.660–1.097]; p = 0.2125}, Black/African American [OR 0.807 (95% CI, 0.651–1.001); p = 0.0508], Hispanic/Latino [OR 0.957 (95% CI, 0.824–1.154); p = 0.7676], Other race [OR 0.957 (95% CI, 0.627–1.461); p = 0.8376]. In the multivariable analysis, age [OR 0.995 (95% CI, 0.991–1.000); p = 0.0309] and female gender [OR 1.231 (95% CI, 1.090–1.390); p = 0.0008] were associated with the use of regional anesthesia. Conclusion In this single-institution retrospective study of adults who had undergone major open abdominal surgery, the use of regional anesthesia was not associated with race or ethnicity. In the multivariable analysis, age and female gender were associated with the use of regional anesthesia.